STRATEGIC ENVIRONMENTAL ASSESSMENT OF THE ADJUSTMENT PROCESS OF THE CITY MASTERPLAN TO THE SARDINIAN REGIONAL LANDSCAPE PLAN: THE CASE OF CITY MASTERPLAN OF ALGHERO, SARDINIA (ITALY) - Federica Isola; Cheti Pira (European Regional Science Association (ERSA), 2011)
Strategic Environmental Assessment (SEA) in the context of the enactment of the Directive 2001/42/CE is at the core of the adjustment process of provincial and city Masterplan to the Sardinian Regional Landscape Plan (RLP). SEA is a fundamental instrument for the environmental integration during the elaboration and adoption of plans; SEA offers an opportunity to bring about a real change of attitude and culture at strategic levels into strategic decision-making process. In this context, this paper adopted a critical observation relating to the Sardinian landscape planning, in particular trough the analysed of the adjustment process of city Masterplan of Alghero to the Sardinian RLP. The critical aspects which emerged in the adjustment phases are to be considered in a scenario which is common among those territorial and normative contexts to which the Directive should be applied. In particular the situation which is represented in the case study intends to highlight the urgent need for a Sardinian planning legislation reform. This would positively influence the final evaluation of the effects of the plan on the landscape; in particular, this would make up for the flaws in the outdated traditional approaches, based on the dualism between urban and landscape development planning. This would also unify the phases of management of territory, thus mitigating the contrasts inherent in the enactment process, currently under way.
Keywords: 330; Territorial Planning; Urban Planning; Strategic Environmental Assessment (SEA)